The Role of Business in the Empowerment of Women in Developing Countries - Murteira, Susana (2011)
The topic of this management project is the role of business in the empowerment of women in developing countries. Through the scoping of business initiatives to empower women in developing countries among UK and USA companies signatories of the UN Global Compact, the aim was to answer the question on what business initiatives are under way to empower women in developing countries among these companies. Moreover, through interviews with a few of these companies, the aim was to extract some lessons learned and steps for the future so as to provide practical guidance for companies seeking to run initiatives to empower women in developing countries. 60 within 416 companies were found to be running initiatives to empower women in developing countries. These initiatives were categorised according to their area of intervention: workplace, marketplace and community. Within the community, initiatives are spread among areas such as education, health, support to women’s organisations, and advocacy for women’s issues. The main motive for selecting women’s empowerment in developing countries as the focus for the initiatives is giving back to the community. The initiatives are mainly run in partnership with either local or global organisations. From the findings and their implications, further research on the topics of motives and models of partnership regarding business initiatives to empower women in developing countries is suggested. In addition, business universes beyond UK and USA companies signatories of the UN Global Compact are advanced as further options to gain a wider understanding on the topic of business role in the empowerment of women in developing countries.